Punk style - Sklar, Monica (Subcultural style series, 2012)
'Punk Style' examines the dress of this incredibly diverse, and influential subculture and its impact on mainstream fashion. Taking a comprehensive approach, the book includes a historical overview, a discussion of motivations behind dress practices, and a review of fashion cycles and merchandising methods.